2011
DOI: 10.1093/nar/gkr444
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation insights into regulatory T cells: expression profiling and FoxP3 occupancy in Human

Abstract: Regulatory T-cells (Treg) play an essential role in the negative regulation of immune answers by developing an attenuated cytokine response that allows suppressing proliferation and effector function of T-cells (CD4+ Th). The transcription factor FoxP3 is responsible for the regulation of many genes involved in the Treg gene signature. Its ablation leads to severe immune deficiencies in human and mice. Recent developments in sequencing technologies have revolutionized the possibilities to gain insights into tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 56 publications
2
82
0
Order By: Relevance
“…They found that the expression of the DUSP6 and DUSP4 phosphatases, which selectively inactivate ERK kinases, is up-regulated in Treg cells (23). Consistent with this, CD3/CD28-mediated activation of the MEK-ERK pathway is largely impaired in regulatory T-cell lines from human cord blood (39).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…They found that the expression of the DUSP6 and DUSP4 phosphatases, which selectively inactivate ERK kinases, is up-regulated in Treg cells (23). Consistent with this, CD3/CD28-mediated activation of the MEK-ERK pathway is largely impaired in regulatory T-cell lines from human cord blood (39).…”
Section: Discussionmentioning
confidence: 80%
“…Stable Foxp3 expression in the progeny of Treg cells is ensured by a positive feedback loop comprising the CNS2 (also known as TSDR) region in the Foxp3 gene locus, the Cbf␤-Runx1 transcription factor, and Foxp3 itself, in which CNS2, Cbf␤-Runx1, and Foxp3 bind to each other to form a transcription complex (7,(21)(22)(23)(24). Treg cells lacking CNS2, Cbf␤, or Runx1 gradually lose or down-regulate Foxp3 expression, indicating that defects in this positive feedback loop promote Treg cell instability (21,22).…”
Section: Cd25mentioning
confidence: 99%
“…Using these criteria, a list of putative VV receptors was made according to mass spectrometry or transcriptome sequencing (RNA-seq) data available from previous studies ( Table 1). These proteins were selected based on their presence in monocyte DRMs (28), the upregulation on CD14 high CD16 Ϫ monocytes versus CD14 low CD16 ϩ monocytes (29), and the upregulation on activated T cells versus naive T cells (30).…”
Section: Vv Differentially Binds To Primary Human Leukocyte Subsetsmentioning
confidence: 99%
“…We have recently shown that several of these TFs make up, together with FOXP3, a genetic switch that locks in the Treg phenotype (13). The transcriptome of Treg cells has been less extensively studied in humans although early studies indicate that several of the more prominent members of the mouse Treg signature are also differentially expressed in human Treg cells (18)(19)(20).…”
mentioning
confidence: 99%